RETRACTED: Research on the institutional environment of the green economy: foreign and domestic experience - Makhosheva Salima; Kandrokova Marina; Yandieva Lyudmila; Uyanaeva Khalimat (BIO Web of Conferences, 2024)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001